Квазипериодические возмущения в среднеширотной ионосфере по данным радара некогерентного рассеяния в Харькове и мировой сети ионозондов - Ляшенко, М. В. (НТУ "ХПИ", 2004)
Analysis of worldwide ionosonde net and Kharkov incoherent scatter radar critical frequency variations and other ionospheric parameters is presented. It is shown that in ionosphere in different heliogeophysical conditions are present the quasi wave processes with different temporary and spatial scales. It is obtained that wave processes can make significant contribution to response of the ionosphere on different intensity magnetic disturbances
Keywords: электронная концентрация; магнитные бури; волновые возмущения; атмосфера; радар HP